The Rise of Keto Man: The Myth of Self-Sufficiency - Wilson, Genevieve (Imaginations)

(untitled) (York University, 2024)
This paper examines how the keto (ketogenic) diet comes to meet the social and political needs and desires that go unmet in the context of neoliberalism. By tracking the ideology and rhetoric that emerges from personal anecdotes of people reliant on a meat based diet – with a specific focus to online platforms – I situate the diet as engaging with and reproducing a male chauvinistic ideology. I suggest that the person who finds themselves on keto wants to invest in themselves to contrast the anxiety and precarity that they face in a neoliberal society. I call this figure Keto Man.